2001
DOI: 10.1046/j.1365-2141.2001.03033.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of autologous stem cell transplant in multiple myeloma patients with renal failure

Abstract: Summary. Data are presented on 81 multiple myeloma (MM) patients with renal failure (creatinine . 176´8 mmol/ l) at the time of autologous stem cell transplantation (auto-SCT), including 38 patients on dialysis. The median age was 53 years (range: 29±69) and 26% had received more than 12 months of prior chemotherapy. CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
2
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(231 citation statements)
references
References 40 publications
11
211
2
7
Order By: Relevance
“…[19][20][21] Conversely, Parikh et al 22 evaluated outcomes of 46 patients with MM and renal failure and showed that MEL200 was not associated with increased toxicity and renal function improved in 32% of patients. Despite these conflicting data, major working groups such as IMWG and ABSMT recommend reducing the dose from 200 to 100-140 mg/m 2 in patients with CrCl o 60 mL/min based on decreased tolerability in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Conversely, Parikh et al 22 evaluated outcomes of 46 patients with MM and renal failure and showed that MEL200 was not associated with increased toxicity and renal function improved in 32% of patients. Despite these conflicting data, major working groups such as IMWG and ABSMT recommend reducing the dose from 200 to 100-140 mg/m 2 in patients with CrCl o 60 mL/min based on decreased tolerability in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Median time to neutrophil engraftment was 10 (range 7-12) and 9 (range 8-13) days in patients with CrCl o 60 mL/min and ⩾ 60 mL/min, respectively (P = 0.008). Median time to platelet engraftment was 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)) and 10 (8-18) days in each group, respectively (P o 0.001). The median duration of hospitalization was significantly longer in patients with RI (14 (range 12-36) versus 16 (range 11-47) days, P = 0.02).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In summary, high melphalan dose (expressed as mg/kg or mg/m 2 ) and/or renal impairment are significant risk factors for severe oral mucositis. [16][17][18][19][20] However, high-dose intensity also is associated with improved disease response. 21,22 Palumbo et al 23 reported improved PFS with melphalan 200 mg/m 2 rather than melphalan 100 mg/m 2 , but increased gastrointestinal toxicity was noted.…”
Section: Indirect Indicators Of Melphalan Pharmacodynamicsmentioning
confidence: 99%
“…33 Badros et al 20 examined melphalan toxicity in 81 subjects undergoing autotransplantation in the setting of renal failure, including 38 patients receiving dialysis. Sixty patients (27 undergoing dialysis) received melphalan 200 mg/m 2 ; 21 (11 on dialysis) subsequently were treated at a lower melphalan dose of 140 mg/m 2 .…”
Section: Dosing In Renal Impairmentmentioning
confidence: 99%
“…Moreover, very few data on the outpatient ASCT management of MM patients with impaired renal function or other comorbidities are reported. 49,50 The expert panel selected a list of major criteria to enroll patients in an outpatient ASCT program. A set of specific questions was answered by each panel members and the results with the final list of inclusion/exclusion criteria are reported in the Supplementary File.…”
Section: Operative Questionsmentioning
confidence: 99%